The Role of Information in Strategic Planning and Decision Making: Overview on Economic Organizations in Oman - Khalfan Zahran AlHijji; Nabhan Harith AlHarrasi; Huda Salem Alissaee (Universitas Hayam Wuruk Perbanas, 2018)
This study aims to investigate the issue of the role of information in strategic planning and decision making in Omani economic organizations. It also attempts to understand the process and the importance of information in decision making. A qualitative method was applied to achieve the study objectives. Thirty participants from eleven organizations were selected for in-depth interviews. Nineteen of the participants are general directors, seven are directors, while the rest are advisors at their organizations. All interviews were analyzed by using thematic analysis. The results show that Omani government economic organizations usually take two types of decisions: technical routine decisions that are regularly made by managers and other decision makers and strategic decisions directed toward achieving the future aspirations of the organization. The type of decision is affected by the level of management and time of making the decision. Participants form different economic organizations are agreed that there should be a clear strategy for making and evaluating decisions, starting from gathering and analyzing relevant data and following through to implementation of the final decision.